Phenolic Profile and Cholinesterase Inhibitory Properties of Three Chilean Altiplano Plants: Clinopodium gilliesii (Benth.) Kuntze [Lamiaceae], Mutisia acuminata Ruiz & Pav. var. hirsuta (Meyen) Cabrera, and Tagetes multiflora (Kunth) [Asteraceae] - Carlos Fernández-Galleguillos; Felipe Jiménez-Aspee; Daniel Mieres-Castro; Yeray A. Rodríguez-Núñez; Margarita Gutiérrez; Luis Guzmán; Javier Echeverría; Claudia Sandoval-Yañez; Oscar Forero-Doria (Plants, 2023)
This research aimed to identify the phenolic profile and composition of the aerial parts of three native species used in traditional medicine in the Andean Altiplano of northern Chile: Clinopodium gilliesii (Benth.) Kuntze [Lamiaceae] (commonly known as Muña-Muña), Mutisia acuminata Ruiz & Pav. var. hirsuta (Meyen) Cabrera [Asteraceae] (commonly known as Chinchircoma), and Tagetes multiflora (Kunth), [Asteraceae] (commonly known as Gracilis), as well as to evaluate their potential inhibitory effects against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Polyphenolic enriched-extracts (PEEs) of the species were prepared and analyzed and the main components were quantified using HPLC-DAD. In total, 30 phenolic compounds were identified and quantified in all species, including simple phenolics, hydroxycinnamic acids, flavan-3-ols (monomers and polymers), flavanones, and flavonols. In addition, other main phenolics from the extracts were tentatively identified by ESI-MS-MS high-resolution analysis. T. multiflora extract showed the greatest anti-AChE and BChE activity in comparison with C. gilliesii and M. acuminata extracts, being the anti-AChE and BChE activity weak in all extracts in comparison to galantamine control. To comprise to better understand the interactions between cholinesterase enzymes and the main phenolics identified in T. multiflora, molecular docking analysis was conducted.